Differential Toxicity of DNA Adducts of Mitomycin C. (13th July 2010) - Bargonetti, Jill; Champeil, Elise; Tomasz, Maria
Abstract : The clinically used antitumor agent mitomycin C (MC) alkylates DNA upon reductive activation, forming six covalent DNA adducts in this process. This review focuses on differential biological effects of individual adducts in various mammalian cell cultures, observed in the authors' laboratories. Evidence is reviewed that various adducts are capable of inducing different cell death pathways in cancer cells.This evidence is derived from a parallel study of MC and its derivatives 2, 7-diaminomitosene (2, 7-DAM) which is the main metabolite of MC and forms two mono-adducts with DNA, and decarbamoyl mitomycin C (DMC), which alkylates and cross-links DNA, predominantly with a chirality opposite to that of the DNA adducts of MC. 2, 7-DAM is not cytotoxic and does not activate the p53 pathway while MC and DMC are cytotoxic and able to activate the p53 pathway. DMC is more cytotoxic than MC and can also kill p53-deficient cells by inducing degradation of Checkpoint 1 protein, which is not seen with MC treatment of the p53-deficient cells. This difference in the cell death pathways activated by the MC and DMC is attributed to differential signaling by the DNA adducts of DMC. We hypothesize that the different chirality of the adduct-to-DNA linkage has a modulating influence on the choice of pathway.